Steroids in villous atrophy: opening a can of worms?. Issue 3 (21st May 2012) - Lee, Lennard; Blaker, Paul; Gill, Baljit; Lucas, Sebastian; Muir, Victoria; Irving, Peter M
Abstract : A 60 year old man presented to the emergency department with septic shock and respiratory distress. He noted significant weight loss over the last 6 months with associated postprandial bloating. Endoscopy demonstrated partial villous atrophy. He had been on a gluten free diet, received empirical treatment for giardiasis and was receiving treatment with high dose systemic steroids for retroperitoneal fibrosis. This case discusses histology findings, differentials and reason for this acute presentation.